Symptoms, disease severity and treatment of adults with a new diagnosis of severe aortic stenosis. Issue 22 (13th July 2019) - Frey, Norbert; Steeds, Richard Paul; Rudolph, Tanja K; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Lloyd, Guy; Bortone, Alessandro Santo; Hauptmann, Karl Eugen; Clerici, Alberto; et al.
Abstract : Objective: Contemporary data on patients with previously undiagnosed severe aortic stenosis (AS) are scarce. We aimed to address this gap by gathering data from consecutive patients diagnosed with severe AS on echocardiography. Methods: This was a prospective, multicentre, multinational, registry in 23 tertiary care hospitals across 9 European countries. Patients with a diagnosis of severe AS were included using echocardiography (aortic valve area (AVA) <1 cm 2, indexed AVA <0.6 cm 2 /m 2, maximum jet-velocity (Vmax ) >4 m/s and/or mean transvalvular gradient >40 mm Hg). Results: The 2171 participants had a mean age of 77.9 years and 48.0% were female. The mean AVA was 0.73 cm 2, Vmax 4.3 m/s and mean gradient 47.1 mm Hg; 62.1% had left ventricular hypertrophy and 27.3% an ejection fraction (EF) <50%. 1743 patients (80.3%) were symptomatic (shortness-of-breath 91.0%; dizziness 30.2%, chest pain 28.9%). Patients had a EuroSCORE II of 4.0; 25.3% had a creatinine clearance <50 mL/min, and 3.2% had an EF <30%. Symptomatic patients were older and had more comorbidities than asymptomatic patients. Despite European Society of Cardiology 2017 valvular heart disease guideline class I recommendation, in only 76.2% a decision was made for an intervention (transcatheter 50.4%, surgical aortic valve replacement 25.8%). In asymptomatic patients, 57.7% with a class I/IIa indication were scheduled for a procedure, while 36.3% patients without an indication had their valve replaced. Conclusions: The majority of patients with severe AS presented at an advanced disease stage. Management of severe AS remained suboptimal in a significant proportion of contemporary patients with severe AS. Trial registration number: NCT02241447;Results.